2008
DOI: 10.1002/ajmg.b.30847
|View full text |Cite
|
Sign up to set email alerts
|

Failure to confirm genetic association of the CHI3L1 gene with schizophrenia in Japanese and Chinese populations

Abstract: Recently, three common polymorphisms in the promoter region of the Chitinase 3-Like 1 (CHI3L1) gene, rs6691378, rs10399805 and rs4950928, have been identified as schizophrenia predisposing single nucleotide polymorphisms (SNPs) in the Han Chinese population. The at-risk haplotype comprising these SNPs was also related to decreased expression of CHI3L1 in peripheral blood cells. In contrast, two independent postmortem brain studies have reported elevated expression of the transcript in the hippocampus and prefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, two genetic studies claimed that variants in the promoter of CHI3L1 are associated with susceptibility to schizophrenia [ 19 , 20 ]. However, a more recent study failed to confirm a genetic association between CHI3L1 and schizophrenia in Japanese and Chinese populations [ 21 ]. Overall, our results showed only occasional CHI3L1 positive cells in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two genetic studies claimed that variants in the promoter of CHI3L1 are associated with susceptibility to schizophrenia [ 19 , 20 ]. However, a more recent study failed to confirm a genetic association between CHI3L1 and schizophrenia in Japanese and Chinese populations [ 21 ]. Overall, our results showed only occasional CHI3L1 positive cells in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rs10399805 polymorphism has been found to be associated with diseases such as atopy and schizophrenia 32 , 54 . Regarding rs6691378 and rs10399805, the genetic contribution of CHI3L1 to schizophrenia has been shown to vary, despite it being mechanistically involved in the disease process 55 . In addition, our previous study demonstrated that the CHI3L1 SNPs rs6691378 and rs10399805 and the CHI3L1 haplotype correlate with the development of cervical precancerous lesions and invasive cancer 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of CHI3L1 is unknown; however, it is believed to play a role in cell survival by mediating cellular response to physiological insults. The associations were not replicated in a study including Chinese and Japanese individuals (Yamada et al, 2009). In addition, the induction of CHI3L1 is thought to be indicative of tissue remodelling in rheumatoid joints (Johansen et al, 1993), and it is speculated that this role may extend to remodelling of neuronal connections in the brain (Chung et al, 2003).…”
Section: Introductionmentioning
confidence: 90%